Toughness and microstructure stability in hot-working tool steels subjected to washout in molten aluminium. (17th June 2008) - Perrone, R.; Ugues, D.; Torres, E.; Regina, U., M. Rosso
A basic and a modified AISI H11 steels were selected for the research. Impact toughness and microstructure in the quenched and tempered state were analysed. Cyclic immersions in molten aluminium with the aim of simulating the washout, typical of aluminium die casting tools, were applied. Optical and electronic microscopy analysis were used to evaluate damages provided by washout on the specimen surface. XRD measurements were applied to identify the corrosion and soldering products deposited on the steel surface. Microhardness profiles were recorded before and after the test to assess any softening effect. Impact tests were performed on specimens subjected to increasing immersion cycles. A detailed study of the evolution of damages provided by cyclic contact with molten aluminium is presented for two hot working tool steels. An analysis of the modulation of the impact toughness as a function of the number of immersions in molten aluminium is reported.